TÍNH
5/6+5/7+5/42
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
6 x 6 = 36 63 : 7 = 9 7 x 5 = 35 6 x 7 = 42
7 x 7 = 49 48 : 6 = 8 35 : 7 = 5 42 : 6 = 7
5 x 5 = 25 49 : 7 = 7 35 : 5 = 7 42 : 7 = 6
6 x 6 = .36.... 63 : 7 = 9..... 7 x 5 = .35...... 6 x 7 = ..42...
7 x 7 = ..42... 48 : 6 = ..8... 35 : 7 = ...5.. 42 : 6 = ..7...
5 x 5 = ...25.. 49 : 7 = .7.... 35 : 5 = ...7.. 42 : 7 = ..6...
hok tốt
Học sinh nhẩm và ghi kết quả như sau:
7 x 5 = 35
7 x 6 = 42
7 x 2 = 14
7 x 4 = 28
35 : 7 =5
42 : 7 = 6
14 : 7 = 2
28: 7 =4
35 : 5 = 7
42 : 6 = 7
14 : 2 = 7
28 : 4 = 7
9 × 5 = 45
6 × 4 = 24
63 : 7 = 9
40 : 5 = 8
8 × 8 = 64
7 × 5 = 35
56 : 8 = 7
42 : 6 = 7
6 ´ 8= 48 |
28 : 4 = 7 |
35 : 5 = 7 |
7 ´ 9 = 63 |
56 : 7 = 8 |
4 ´ 6 = 24 |
5 ´ 4 = 20 |
42 : 6 = 7 |
36 : 6 = 6 |
3 ´ 8 = 24 |
45: 5 = 9 |
49 :7 = 7 |
Học sinh nhẩm và ghi kết quả như sau:
6 x 9 = 54
28 : 7 = 4
7 x 7 = 49
56 : 7 = 8
7 x 8 = 56
36 : 6 = 6
6 x 3 = 18
48 : 6 = 8
6 x 5 = 30
42 : 7 = 6
7 x 5 = 35
40 : 5 = 8
3: \(=20-12-8+12=20-8=12\)
5: \(=-18-42-21-35=-116\)
3: \(=-15+18-12+8=-27+26=-1\)
2: \(=-12+21-15+10=9-5=4\)
2) -3(4 - 7) + 5(-3 + 2)
= -3.4 + 3.7 - 5.3 + 5.2
= -12 + 21 -15 + 10
= 31 - 27
= 4
4) -5(2 - 7) + 4(2 - 5)
= -5.2 + 5.7 + 4.2 - 4.5
= -10 + 35 + 8 - 20
= 38 - 30
= 8
70 : 7 = 10
28 : 7 =4
30 : 6 = 5
8 : 2 = 9
63 : 7 = 9
42 : 6 = 7
35 : 5 = 6
27 : 3 = 9
14 : 7 = 2
42 : 7 = 6
35 : 7 = 5
56 : 7 = 8.
\(\dfrac{6}{7}+\dfrac{7}{8}=\dfrac{48}{56}+\dfrac{49}{56}=\dfrac{97}{56}\)
\(\dfrac{4}{5}-\dfrac{2}{3}=\dfrac{12}{15}-\dfrac{10}{15}=\dfrac{2}{15}\)
\(\dfrac{1}{5}:\dfrac{2}{7}=\dfrac{1}{5}.\dfrac{7}{2}=\dfrac{7}{10}\)
\(\dfrac{4}{7}-\dfrac{11}{42}=\dfrac{24}{42}-\dfrac{11}{42}=\dfrac{13}{42}\)
\(\dfrac{2}{3}+\dfrac{3}{51}=\dfrac{34}{51}+\dfrac{3}{51}=\dfrac{37}{51}\)
Tính
\(\dfrac{6}{7}+\dfrac{7}{8}=\dfrac{48}{56}+\dfrac{49}{56}=\dfrac{48+49}{56}=\dfrac{97}{56}\)
\(\dfrac{4}{5}-\dfrac{2}{3}=\dfrac{12}{15}-\dfrac{10}{15}=\dfrac{12-10}{15}=\dfrac{2}{15}\)
\(\dfrac{1}{5}:\dfrac{2}{7}=\dfrac{1}{5}.\dfrac{7}{2}=\dfrac{1.7}{5.2}=\dfrac{7}{10}\)
\(\dfrac{4}{7}-\dfrac{11}{42}=\dfrac{24}{42}-\dfrac{1}{42}=\dfrac{24-1}{42}=\dfrac{23}{42}\)
\(\dfrac{2}{3}+\dfrac{3}{51}=\dfrac{34}{51}+\dfrac{3}{51}=\dfrac{34+3}{51}=\dfrac{37}{51}\)
35/21
TINH MA